2015
DOI: 10.1155/2015/281287
|View full text |Cite
|
Sign up to set email alerts
|

Osteoimmunology: Major and Costimulatory Pathway Expression Associated with Chronic Inflammatory Induced Bone Loss

Abstract: The field of osteoimmunology has emerged in response to the range of evidences demonstrating the close interrelationship between the immune system and bone metabolism. This is pertinent to immune-mediated diseases, such as rheumatoid arthritis and periodontal disease, where there are chronic inflammation and local bone erosion. Periprosthetic osteolysis is another example of chronic inflammation with associated osteolysis. This may also involve immune mediation when occurring in a patient with rheumatoid arthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 113 publications
(192 reference statements)
2
92
0
2
Order By: Relevance
“…Our results are partly compatible with available literature. RANKL/OPG ratio has been associated with bone destruction (5,20,36,38). Supporting this, van Tuyl et al suggested that RANKL/ OPG and collagen terminal I and II (CTX) were strong predictors of rapid and persistent disease activity in RA (39).…”
Section: Discussionmentioning
confidence: 94%
“…Our results are partly compatible with available literature. RANKL/OPG ratio has been associated with bone destruction (5,20,36,38). Supporting this, van Tuyl et al suggested that RANKL/ OPG and collagen terminal I and II (CTX) were strong predictors of rapid and persistent disease activity in RA (39).…”
Section: Discussionmentioning
confidence: 94%
“…Although proinflammatory cytokines, such as IL-1, IL-6, and TNF-a, are critical in bone metabolism, these cytokines have also been attributed to the pathogenesis of osteoporosis and an increased risk of fracture [18]. Studies have shown that chronic inflammation can mediate bone loss through the disturbance of the receptor activator of nuclear factor j-B ligand (RANKL)-RANK-osteoprotegerin (OPG) axis, an essential regulator in bone metabolism [19,20]. Except for inflammatory autoimmune diseases, such as RA and systemic lupus erythematosus [21], an increased risk of fracture has been reported for such medical conditions as diabetes mellitus and chronic kidney disease [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…directly in the periodontium. 22,23 Clinical studies have shown a high expression of these markers in patients with periodontal disease. 21 These cytokines may induce bone resorption, affecting the production of essential osteoclast differentiation and the resulting bone destruction.…”
mentioning
confidence: 99%
“…The stimulatory factors regulating this process are cytokines such as interleukin-1 (IL-1), macrophage colony-stimulating factor (MCSF), monocytes and T cells. 22,24 The treatment of periodontal disease is based on virulence factors, the microorganisms that are established in the processes of health and disease; therefore, the treatments must aim to control these microorganisms. 4,8,9 It is necessary to understand the role of bacterial biofilm in the etiology of periodontal diseases, as the severity and progression of these diseases are determined in large part by factors related to the host's response.…”
mentioning
confidence: 99%